2007
DOI: 10.1037/0022-006x.75.5.693
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of depressive symptoms in adolescents: A randomized trial of cognitive-behavioral and interpersonal prevention programs.

Abstract: This study evaluated the efficacy of 2 programs for preventing depressive symptoms in adolescents. Participants were 380 high school students randomly assigned to a cognitive-behavioral program (CB), an interpersonal psychotherapy-adolescent skills training program (IPT-AST), or a no-intervention control. The interventions involved eight 90-min weekly sessions run in small groups during wellness classes. At postintervention, students in both the CB and IPT-AST groups reported significantly lower levels of depr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
188
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 213 publications
(201 citation statements)
references
References 71 publications
11
188
0
2
Order By: Relevance
“…Cognitive changes mean children have the ability for more complex thought, are more able to verbalize their experiences and emotions and are developing their own sense of right and wrong. Evidence suggests that middle childhood is a key time for targeting preventative interventions (Dadds, Spence, Holland, Barrett, & Laurens, 1997;Horowitz, Garber, Ciesla, Young, & Mufson, 2007), in part because research across the lifespan has established that self-esteem becomes more stable in adolescence (defined in this study as 12-17 years) and early adulthood (Trzesniewski, Donnellan, & Robins, 2003). That finding further supports early adolescence as a key time in a child's development for interventions aimed at promoting self-esteem before it stabilizes.…”
Section: Methodssupporting
confidence: 67%
See 2 more Smart Citations
“…Cognitive changes mean children have the ability for more complex thought, are more able to verbalize their experiences and emotions and are developing their own sense of right and wrong. Evidence suggests that middle childhood is a key time for targeting preventative interventions (Dadds, Spence, Holland, Barrett, & Laurens, 1997;Horowitz, Garber, Ciesla, Young, & Mufson, 2007), in part because research across the lifespan has established that self-esteem becomes more stable in adolescence (defined in this study as 12-17 years) and early adulthood (Trzesniewski, Donnellan, & Robins, 2003). That finding further supports early adolescence as a key time in a child's development for interventions aimed at promoting self-esteem before it stabilizes.…”
Section: Methodssupporting
confidence: 67%
“…Our review found that universal interventions are typically not universally effective, with greater benefits being measured in those with greater needs at baseline (Dadds et al, 1997;Horowitz et al, 2007). Additionally, the majority of interventions described demonstrated the effectiveness of Cognitive Behavior Therapy (CBT) at modifying an individual's internal cognitions to reduce symptoms of anxiety in children (Cresswell et al, 2014;Dadds et al, 1997;Horowitz et al, 2007).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[2] It also compares positively to the effect sizes for other school-based interventions. [4,29] This is an important finding as it indicates that a self-directed intervention delivered via the Internet may be as effective at reducing depressive symptoms as more resource intense face-to-face interventions. As Internet delivery offers flexibility and sustainability, the findings suggest that MoodGYM could be a valuable resource for reducing distress and depressive symptoms in adolescents.…”
Section: Discussionmentioning
confidence: 90%
“…In their meta-analytic review, Horowitz and Garber (2007) suggested that because depression is such a complex problem, multi-component programs are likely to be the most effective. They further suggested that clinical trials should examine hypothesized mediators, such as checking whether the techniques trained (e.g., social skills, attributional training, problem-solving skills) improved following the implementation of the program, and verifying that these were, in fact, the active ingredients responsible for the improvement in depressive symptoms.…”
Section: Future Directionsmentioning
confidence: 99%